Antiulcerogenic Effect of Zataria multiflora Boiss. on Cysteamine Induced Duodenal Ulcer in Rats: Antiulcerogenic effect of Zataria multiflora - Minaiyan, Mohsen; Ghannadi, Alireza; Salehi, Esmaeil (Iranian Journal of Pharmaceutical Sciences, 2005)
Research advances during recent years offer new insight into therapy and the prevention of gastrointestinal ulcers by using medicinal plants. Flavonoids, tannins, triterpenoids, fatty acids and essential oils are among the most effective herbal constituents that have potential antiulcerogenic properties, and most of them could be found in Zataria multiflora. Z. multiflora is one of the indigenous plants of Iran, which is readily available and traditionally used to improve gastrointestinal disorders. In a recent trial, we decided to study the potential antiulcerogenic effects of the plant on an animal model of duodenal ulcer. Hydroalcoholic extract of the plant with doses of 200, 400, 800 and 1200 mg/kg, ranitidine (50 mg/kg), sucralfate (2 g/kg) and 1 ml of the vehicle were administered orally to different groups of male Wistar rats. Two other groups received (i.p.) vehicle (1 ml) and extract (800 mg/kg). Duodenum ulcers were induced by cysteamine HCl and the number of ulcers, area, and finally ulcer index were assessed. Ranitidine and sucralfate resulted in significant reduction in the duodenal mucosal damage for the entire ulcer factors assessed. Increasing doses of the extract resulted in a significant reduction in ulcerated area and index in a dose dependent manner. We concluded that Z. multiflora extract was effective in protecting against duodenal ulceration, and for the larger doses used, the efficacy was comparable with the reference drugs. The mechanism of action couldn’t be clearly proposed for the plant extract, however; the local mucosal enhancement and cytoprotection may be involved.